Cover Feature: Mannose‐Decorated Multicomponent Supramolecular Polymers Trigger Effective Uptake into Antigen‐Presenting Cells (ChemBioChem 9/2018). (19th April 2018) - Straßburger, David; Stergiou, Natascha; Urschbach, Moritz; Yurugi, Hajime; Spitzer, Daniel; Schollmeyer, Dieter; Schmitt, Edgar; Besenius, Pol
Abstract : The cover feature picture shows the supramolecular copolymerisation of a dendritic peptide amphiphile monomer bearing mannosides and a second monomer carrying tetra(ethylene glycol)s and labelled with a Cy3 fluorescent probe. The multicomponent mannose‐decorated copolymers trigger the uptake into macrophages as antigen‐presenting cells that play a key role in the innate immune response. More information can be found in the communication by E. Schmitt, P. Besenius et al. onpage 912 in Issue 9, 2018 (DOI:10.1002/cbic.201800114 )